Mild Chronic Traumatic Encephalopathy Neuropathology in People With No Known Participation in Contact Sports or History of Repetitive Neurotrauma. Issue 7 (6th June 2019) - Iverson, Grant L; Luoto, Teemu M; Karhunen, Pekka J; Castellani, Rudolph J
Abstract: It has been asserted that chronic traumatic encephalopathy (CTE) pathology is only present in former athletes and others who have been exposed to repetitive concussions, subconcussive blows, or both. We hypothesized that CTE pathology would be present in men who had no known history of repetitive neurotrauma. Comprehensive medical record reviews and health surveys completed by a family member were available for the 8 men in this case series, none of whom had known exposure to repetitive neurotrauma but 2 of whom had a history of traumatic brain injury (TBI). Postmortem tissue was immunostained for hyperphosphorylated tau (p-tau) to assess for CTE pathology, Braak stage, and aging-related p-tau. The neuropathologist was blind to age, personal history, and clinical history. Six of the 8 cases (75%) showed p-tau in neurons, astrocytes, and cell processes around small blood vessels in an irregular pattern at the depths of the cortical sulci. The changes were focal and limited in terms of overall extent, and some of the cases had a clearer pattern of pathology and some could be considered equivocal. Two of the 8 cases had a history of TBI and one of them showed CTE pathology. Five of the 6 cases with no known history of neurotrauma appeared to meet consensus criteria for CTE. This study adds to the emerging literature indicating that CTE pathology is present in people not known to have experienced multiple concussions or subconcussive blows to the head.